Utility of Mannheim’s Peritonitis Index in Predicting Outcome of Peritonitis in Patients with Hollow Viscous Perforation - Akash Raya; Aditya Prakash Yadav; Sanjiv Kumar Shahi; Binod Kr Rai (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Peritonitis due to hollow viscous perforation is one of the common causes for emergency surgery requiring immediate surgical intervention. Scoring systems that provide objective descriptions of the patient’s conditions at speciﬁc points in the disease process aid our understanding of these problems. Hence this study is undertaken to study the effectiveness of Mannheim’s peritonitis index in predicting the outcome in peritonitis patient. MATERIAL AND METHODS This study was carried out in Department of Surgery of National Medical College and Teaching Hospital. A total of 44 patients with diagnosis of peritonitis due to hollow viscous perforation over period 2 years was included in this study. History and detailed clinical examination were performed as per the working proforma. Blood investigation was done. Data analysis was done using SPSS (Statistical Package for social sciences) version 25. RESULTS In this study 44 cases of peritonitis due to hollow viscous perforation were included. The mean age of patients was 38.16 ± 21.09 years. Abdominal pain and abdominal distension were most common presentation. MPI scoring system done in all patients depending on preoperative and intra-operative and patients were categorized into three categories, <21, 21 to 29, and >29 where 50% of patients had MPI less than 21, 25% of patient had MPI score 21-29 and 25% of patient had MPI score >29. CONCLUSION MPI scoring system is required to predict the outcome in peritonitis patients and whether the line of management taken is appro- priate or needs to be changed.